Study of Essential Oil Extraction of Rosella Flower Petals (Hibiscus Sabdaíiffa L.) Water Steam Destilation Method - Nunuk Helilusiatiningsih; Titik Irawati; Muhammad Alwi Syahara (MultiTech Publisher, 2023)
Indonesia had a tropical climate, rosella can grow abundantly. The problem that exists is how to extract essential oils from these plants and screen for phytochemicals in plant organs. The aim of the research was to study the extraction of essential oils from rosella flower petals and phytochemical screening, sensory testing of the oil results. The research method is essential oil extraction using water steam distillation, color and aroma analysis using the hedonic method and the DPPH test. The research results are as follows. The yield of essential oils in flower petals is 0.0136% in 1.1 kg of dry material. The color test was 60% very like it, 40% liked it and the aroma test for essential oils was around 55%, they really liked it and 45% liked it, while the panelists didn't like it 0%. Results of analysis of the antioxidant activity of rosella flower petal extract with a concentration of 5 ppm = 30.6%; 10 ppm = 33.7 %; 25 ppm = 41.7 %; 50 ppm = 45 %; 100 ppm = 48.3%; 200 ppm = 57.5 %.